Process state synchronization for mobility support in mobile cloud computing / Ejaz Ahmed - Ejaz, Ahmed (2016)
Mobile Cloud Computing (MCC) enables the resource-constrained mobile devices to execute the compute-intensive mobile applications either in client/server model or through cyber foraging of the tasks to the cloud servers. However, long or permanent network disconnections due to user mobility increase the execution time and in certain cases refrain the mobile devices from getting response back for the remotely performed execution. This research addresses the effect of mobility on application execution for mobile cloud-based interactive applications. We propose Process State Synchronization (PSS) as a mechanism to mitigate the impact of network disconnections on cloud-based interactive mobile applications. We investigate the impact of varying the synchronization interval size of PSS algorithms on the performance of application execution. The sufficient condition and upper bound for the synchronization interval size are also determined that minimize the execution time, computational wastage, synchronization overhead, and energy consumption. Results show that PSS reduces the execution time of applications up to 17% in case of intermittent disconnections. The comparison with existing offloading mechanisms shows that PSS reduces the execution time by up to 47% in case of intermittent network connectivity compared to COMET and by up to 35% in case of optimized VM-based offloading. The improvement in application execution time increases the usability of interactive mobile applications in MCC.